EVALUASI KINERJA SIMPANG BERSINYAL DI KOTA SURABAYA DENGAN MENGGUNAKAN PROGRAM KAJI (Studi Kasus : Ruas Jalan Ngagel Jaya Selatan ) - Tahir, Anas (MEKTEK, 2005)
The growth of vehicle every year give impact to traffic intersection performance. Various resulted by traffic impact arrangement of intersection which is not optimal for example is vehicle queuing, traffic jam , rise in delay time and also increase travel time. This research is conducted in one of Major Street in Surabaya, at Ngagel Jaya Selatan street which intersection between Ngagel Jaya Selatan and Ngagel Jaya Street. In this research, the analysis by using Kapasitas Jalan Indonesia ( KAJI) that program is program share released by Directorate of Urban Road Development (BINKOT). From result of analysis by using KAJI program, got intersection performance at condition in the morning reside at service of level F with queue length is equal to 1531 m, mean number stops of vehicle is 1,23 stops/pcu and mean intersection delay is 195,83 sec/pcu. In the day time happened queue length is equal to 1483 m, mean number stops of vehicle is 1,50 stops/ pcu and mean intersection delay is equal to 151,01 sec/pcu with level of service is F. In the evening got queue length is equal to 2458 m, number stops of vehicle is 2,35 stops/pcu and mean intersection delay is 306,71 sec/pcu with level of service F